2010
DOI: 10.1590/s0103-90162010000500005
|View full text |Cite
|
Sign up to set email alerts
|

Intestinal histomorphology in Pseudoplatystoma fasciatum fed bovine colostrum as source of protein and bioactive peptides

Abstract: Histological responses of the intestine are key for evaluating nutritional value of feed ingredients, since the organ is not only the chief site of feed digestion and nutrient absorption but also plays an important immunological function. Histomorphological alterations were evaluated in the intestine of juvenile striped catfish, Pseudoplatystoma fasciatum, fed diets containing 0 (control), 10 or 20% inclusion of lyophilized bovine colostrum (LBC), as source of protein or bioactive peptides, for either 30 or 60… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
8
0
9

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1
1

Relationship

3
6

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 35 publications
1
8
0
9
Order By: Relevance
“…Thus, other sources of protein with high quality and good market availability need to be explored. Bovine colostrum has high levels of nutrients, containing approximately 41-140 g L À1 of crude protein and 39-44 g L À1 of fat, for this reason, it has been investigated as an alternative management for several species, including sheep, goats, pigs, rodents and fish (Huguet, S eve, Le Dividich & Le Hu€ erou-Luron 2006;Boudry & Thewis 2009;Lima, Pauletti, Susin & Machado-Neto 2009;Moretti, Kindlein, Pauletti & Machado-Neto 2010;Rodrigues, Pauletti, Kindlein, Delgado, Cyrino & Machado-Neto 2010;Bodammer, Maletzki, Waitz & Emmrich 2011;Moretti, Nordi, Lima, Pauletti, Susin & Machado-Neto 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Thus, other sources of protein with high quality and good market availability need to be explored. Bovine colostrum has high levels of nutrients, containing approximately 41-140 g L À1 of crude protein and 39-44 g L À1 of fat, for this reason, it has been investigated as an alternative management for several species, including sheep, goats, pigs, rodents and fish (Huguet, S eve, Le Dividich & Le Hu€ erou-Luron 2006;Boudry & Thewis 2009;Lima, Pauletti, Susin & Machado-Neto 2009;Moretti, Kindlein, Pauletti & Machado-Neto 2010;Rodrigues, Pauletti, Kindlein, Delgado, Cyrino & Machado-Neto 2010;Bodammer, Maletzki, Waitz & Emmrich 2011;Moretti, Nordi, Lima, Pauletti, Susin & Machado-Neto 2012).…”
Section: Introductionmentioning
confidence: 99%
“…It is underlined by the submucosa, the circular and longitudinal muscle layers, and the outer serosa (Matos, Oliveira, Gomes, & Silva, 2017). Hybrid catfish differs on the absence of submucosa layer (Rodrigues et al, 2010).…”
mentioning
confidence: 99%
“…Muscle layer thickness has been related to the segment, species, feeding habits and concentration of protein in the diet (Cao & Wang ; Makino ). Rodrigues, Pauletti, Kindlein, Cyrino, Delgado and Machado‐Neto () observed that the inclusion of lyophilized bovine colostrum in the diet of juveniles of cacharas P. fasciatum for either 30 or 60 days, fed to apparent satiation, twice daily, observed effect of LBC in three segments of the intestine. In the present study, fish from different treatments did not display differences in muscle indicating that the colostrum, lacteal secretion rich in bioactive factors as IGF‐I and EGF‐I, did not influence the development of muscular layer of juvenile dourado.…”
Section: Discussionmentioning
confidence: 99%